STUDENTS’ PERCEPTION OF TEACHER-MADE VIDEOS DURING ONLINE LEARNING - Ruslan, Zumrah Magfirah; Muhayyang, Maemuna; Sofyan, Ryan Rayhana (Universitas Negeri Makassar, 2023)
This study aims to explore students’ perceptions of teacher-made videos during online learning. The researcher applies a descriptive qualitative method to achieve the research objective. The data were collected in the form of interviews. The subjects of the research were 30 students of grade IX SMP Negeri 1 Bulukumba academic 2021/2022. The subjects were chosen by using a simple random technique. Based on the result of the study, students’ perceptions are divided into positive and negative perceptions. The positive perceptions include interesting and motivating, easy to understand, helpful, and improved English skills. The negative perceptions include a lack of interaction, a bad internet connection, and the placement of the camera. Based on the findings, it can be concluded that students’ perceptions are dominated by positive perceptions toward teacher-made videos during online learning. However, there are also negative perceptions stated by students.